Transitioning electricity systems: The environmental benefits and economic cost of repurposing surplus electricity in non-conventional end users. (21st May 2019) - Mukherjee, Ushnik; Haghi, Ehsan; Prabhakaran, Praseeth; Graf, Frank; Fowler, Michael
Abstract: A power grid with a lower global warming impact has the potential to extend its benefits to energy systems that conventionally do not utilize electricity as their primary energy source. This study presents the case of Ontario where the role of complementing policies in transitioning electricity systems is assessed. The policy cost to incentivize surplus low emission electricity via an established mechanism for the transportation sector has been estimated (Electric and Hydrogen Vehicle Incentive Program). It is estimated that the 9056 (4760 battery and 4296 plug-in hybrid) electric vehicles that qualified for incentives from the provincial government at the end of 2016 vehicles cost 732.5-883.9 to reduce a tonne of CO2, e emissions over an eight year lifetime. This is then compared with the potential cost incurred by two power to gas energy hubs that utilize clean surplus electricity from the province to offset emissions within the natural gas sector. The use of hydrogen-enriched natural gas and synthetic natural gas (SNG) offsets emissions at 87.8 and 228.7 per tonne of CO2, e in the natural gas sector. This analysis highlights the potential future costs for incentivizing new clean technologies such as electric vehicles and power to gas energy hubs in jurisdictions with a transitioning electricity system. Highlights: Compared the economics of potential clean energy sinks: Power to Gas and EVs. Established an emission policy cost of the power to gas energy hub concept. Economic cost of reducing emissions higher in transportation sector.